Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1136/bmjopen-2021-056790
|View full text |Cite
|
Sign up to set email alerts
|

Health service costs of treating venous leg ulcers in the UK: evidence from a cross-sectional survey based in the north west of England

Abstract: ObjectivesTo estimate and examine the direct healthcare costs of treating people with open venous leg ulcers in the UK.DesignCost-of-illness study.SettingA cross-sectional survey of nine National Health Service community locales over 2-week periods in 2015/2016.MethodsWe examined the resource use and prevalence of venous leg ulcer treatment in the community. Examination of variation in these obtained costs was performed by ordinary least squares regression. We used additional resource use information from a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…Cohort 3B analysis also showed that VLU were equal second with mixed vascular aetiology leg ulcers insofar as being the most costly chronic wound to treat (Table 5, median A$495/wound). This is broadly consistent with other VLU literature 16,29 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Cohort 3B analysis also showed that VLU were equal second with mixed vascular aetiology leg ulcers insofar as being the most costly chronic wound to treat (Table 5, median A$495/wound). This is broadly consistent with other VLU literature 16,29 .…”
Section: Discussionsupporting
confidence: 93%
“…Collectively, Silverchain nurses managed 41,865 clients with 88,793 wounds. This finding confirms the large number of wounds treated in the community and that wound management often comprises the largest portion of community nurses' workload [13][14][15] and associated costs 16 . It has been previously reported that 70-80% of wounded individuals are treated in the community, and predominately by community nurses who spend 60% of time involved in these activities 7 .…”
Section: Discussionsupporting
confidence: 72%
“…The prevalence of VLU increases with age, doubling among those aged over 65 years [ 4 , 6 ] The typical VLU patient tends to be female, over 65 years old, has a high risk of cardiovascular events, and has obesity [ 7 ]. VLU patients often face ongoing health and quality of life problems [ 6 , 8 ] partially because the treatment itself requires substantial self-management, leading to significant intrapersonal and interpersonal burdens [ 3 , 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…VLUs are a chronic skin condition of the lower limbs, often affecting the elderly and those with chronic health illnesses [1,2]. VLUs affect approximately 1-3% of adults globally [2][3][4]. Furthermore, these wounds tend to be severe; recent evidence suggests that almost 20% of wounds present in aged community samples are VLUs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although diabetes is the leading cause of death associated with chronic ulcers, it is important to note that the mortality risk for those with leg ulcers of any aetiology is greater than controls (9). In addition, due to the high prevalence of chronic ulcers in the UK, affecting nearly 1% of the population and with a point prevalence of 3.2 per 10,000 (10), there is also a great financial burden associated. The cost of chronic wound treatment has been estimated to cost the UK around £100 million-£2 billion annually (10,11) and is expected to reach up to £65 billion across the world by 2024 (12,13).…”
Section: Introductionmentioning
confidence: 99%